PERPUSTAKAAN “SENENG MACA” SEBAGAI SARANA MENINGKATKAN MINAT BACA MASYARAKAT DESA MELUNG - Indah Wijaya Antasari (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2019)
The "Seneng Maca"  library, Melung village was established in 2015 with the intention that the reading interest of Melung villagers increased. This study was conducted with a descriptive qualitative approach, with data collection through observation, and interviews. As a result, with a collection of around 540 copies, the "Seneng Maca" library was visited by mothers while waiting for their children in PAUD and TK schools, school children after they returned (late in the afternoon), and PKK mothers when they were active in the village office near the library. It is recommended to be able to recruit workers or volunteers who have a background in library science, so that the "Seneng Maca" library can be better managed. It is recommended to develop planned collections with sources of village fund allocation. Keywords: Village Community Development, Village Library, Reading Interest.